The future between difficulties and resources: Exploring parents' perspective on young adults with multiple sclerosis. Issue 2 (29th December 2021) - Calandri, Emanuela; Graziano, Federica; Borghi, Martina; Bonino, Silvia
Abstract: Objective: To qualitatively explore parents' representations of the future of their young adult children diagnosed with multiple sclerosis (MS) and of their own future as parents. Background: MS in young adulthood represents a nonnormative transition during the life cycle with a significant impact on the whole family. Previous research examined the perspective of parents having children and adolescents with MS, but there is a lack of knowledge about parenting young adults with MS. Method: Thirteen semistructured interviews were conducted with parents of young adults (aged between 18 and 35 years) with MS, and an inductive content analysis was performed. Results: The future of young people with MS in various domains (study, work, and affective relationships) is deeply influenced by both illness and therapies. Parents' future is conditioned by the illness of their children. Family support and focusing on the present are recognized by parents as resources in coping with MS difficulties. Conclusion: The uncertainty and unpredictability of MS influence parental representations of the future and represent an additional challenge in the difficult transition to adulthood. Implications: The study gives indications for psychological interventions helping parents to cope with their children's illness and to stick to a personal future plan.